2010
DOI: 10.1088/0957-0233/21/7/075102
|View full text |Cite
|
Sign up to set email alerts
|

Traceable characterization of a bending millimetre scale cantilever for nanoforce sensing

Abstract: We have developed and characterized a force measuring system that is able to measure small forces down to 50 nN. The force measuring system and the characterizing method are described, thoroughly tested and analysed. The force measuring system consists of a linear positioner, a bending cantilever and an optical detection system for detecting the bending of the cantilever displacement. Characterization was carried out with a microbalance and a laser interferometer. The characterized measurement range of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, the actual deflection y was defined as the difference between y i and the actual displacements of supports y s along the bending direction, the expression of y could be described in equation ( 2). By simplifying the supports' tip to a regular circle with radius of R s , on basis of the undetermined parameter y ss , the span length l was described as shown in equation (3), where l o denoted the initial span length. To confirm y ss , in consideration that the specimen was in the condition of elastic deformation, the deformation trajectory of the specimen was simplified to a deflection curve.…”
Section: Correction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the actual deflection y was defined as the difference between y i and the actual displacements of supports y s along the bending direction, the expression of y could be described in equation ( 2). By simplifying the supports' tip to a regular circle with radius of R s , on basis of the undetermined parameter y ss , the span length l was described as shown in equation (3), where l o denoted the initial span length. To confirm y ss , in consideration that the specimen was in the condition of elastic deformation, the deformation trajectory of the specimen was simplified to a deflection curve.…”
Section: Correction Methodsmentioning
confidence: 99%
“…Bending tests have been verified to be effective to study the mechanical properties and failure mechanisms of materials combining with the microstructure and load-deflection curve [1]. Especially, the in situ bending test of bulk materials allows not only the evaluation of the mechanical parameters of materials, such as to obtain the bending strength [2], bending elastic modulus [3][4][5] and fracture toughness [6], but also the in situ examination of the deformation development via various imaging devices [2,7]. During the three-point bending testing, a uniaxial bending load is continuously applied on a carefully prepared specimen and the corresponding deflection is recorded.…”
Section: Introductionmentioning
confidence: 99%
“…2 Progress in the micro and nanober formation and in the development of new applications of bers such as sensors, manipulators, and articial muscles, calls for a new level of understanding of the mechanisms of ber actuation with external elds when the force is limited to the micro-and nano-Newton scale. [3][4][5][6][7][8][9] Fiber manipulation and measurement of such small forces require special tools and transducers. 3,4 In the earlier paper, 5 we proposed to use nanober yarns to grab microdroplets of hazardous uids.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Fiber manipulation and measurement of such small forces require special tools and transducers. 3,4 In the earlier paper, 5 we proposed to use nanober yarns to grab microdroplets of hazardous uids. It has been shown that the ber-based grabber can be remotely controlled by applying a nonuniform external magnetic eld 5,6 thus eliminating the need for a special transducer.…”
Section: Introductionmentioning
confidence: 99%